Assessing Suicide Risk in a Pediatric Outpatient Behavioral Health System: A Quality Improvement Report. Issue 3 (14th May 2022) - Soffer, Stephen L.; Lewis, Jason; Lawrence, O'Nisha S.; Marroquin, Yesenia A.; Doupnik, Stephanie K.; Benton, Tami D.
Abstract : Introduction: Standardized suicide risk assessment improves the detection of individuals at risk of suicide. We conducted a quality improvement initiative in a system of outpatient behavioral health practices affiliated with a free-standing children's hospital to implement standardized suicide risk assessment for new patients. Methods: Clinicians received education in suicide risk assessment and were trained to use an evidence-based suicide risk assessment tool, the Columbia Suicide Severity Rating Scale (C-SSRS). We standardized workflow processes and integrated the C-SSRS in the electronic health record with a feature to communicate instances of elevated risk across care teams through a problem list. We analyzed C-SSRS responses and adherence to standardized processes and compared the percentage of patients with a suicide-related item on the problem list before and after implementation. We assessed clinician knowledge through a survey. All patients with identified suicide risk received treatment to reduce their risk of suicide in the context of usual care. Results: For 3, 972 new patient visits occurring postimplementation (November 2016–December 2018), the average monthly adherence to the standardized process was 97.7%. The mean monthly incidence of nonspecific active suicidal thoughts was 16%, aborted suicide attempts were 2%, and actual suicide attempts were 3%. The mean monthly incidence of a suicide-related item documented on the problem list was 5.66% in the postimplementation period compared with 1.47% in the 1-year preimplementation. Clinicians demonstrated statistically significant increases in knowledge about suicide risk factors and assessment. Conclusions: Standardization of suicide risk assessment processes improved detection and documentation of suicide risk in a pediatric outpatient behavioral health setting.